2021
DOI: 10.3389/fmicb.2021.609393
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Alginate Utilization Pathways in Culturable Bacteria Isolated From Arctic and Antarctic Marine Environments

Abstract: Alginate, mainly derived from brown algae, is an important carbon source that can support the growth of marine microorganisms in the Arctic and Antarctic regions. However, there is a lack of systematic investigation and comparison of alginate utilization pathways in culturable bacteria from both polar regions. In this study, 88 strains were isolated from the Arctic and Antarctic regions, of which 60 strains could grow in the medium with alginate as the sole carbon source. These alginate-utilizing strains belon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…Hobbs et al [6] concluded that KdgF catalyzes the conversion of pectin-and alginate-derived 4,5-unsaturated monouronates to linear ketonized forms, a step in uronate metabolism that was previously thought to be spontaneous. In accordance with the significant role of KdgF in alginate metabolism, 21 of 26 alginate-utilizing marine bacterial strains isolated from Arctic and Antarctic marine environments have a gene for KdgF in alginate utilization gene clusters in genomic DNA [25].…”
Section: Enzymatic Formation Of Deh From 45-unsaturated Uronatementioning
confidence: 88%
“…Hobbs et al [6] concluded that KdgF catalyzes the conversion of pectin-and alginate-derived 4,5-unsaturated monouronates to linear ketonized forms, a step in uronate metabolism that was previously thought to be spontaneous. In accordance with the significant role of KdgF in alginate metabolism, 21 of 26 alginate-utilizing marine bacterial strains isolated from Arctic and Antarctic marine environments have a gene for KdgF in alginate utilization gene clusters in genomic DNA [25].…”
Section: Enzymatic Formation Of Deh From 45-unsaturated Uronatementioning
confidence: 88%